A Selective Electrochemical Sensing of Serotonin and Epinephrine at Glassy Carbon Electrode Modulated with Brilliant Green: A Voltammetric Study - Banu, Rukaya; Swamy, B.E. K.; Pandith, Anup (Current Analytical Chemistry, 2023)
In the present investigation, an electrochemical sensing approach based on the electropolymerization modulation of brilliant green on a glassy carbon electrode has been introduced for rapid and sensitive identification of serotonin (SE) and epinephrine (EP) by cyclic and differential pulse voltammetric procedures. Under adequate circumstances, the analytical variable like the pH of the supporting solution, was maintained between the range of 6.2-8.0. Furthermore, the electro-kinetic parameter was surveyed, and the electrode depicted the proportionality between the current intensities with the concentration of analytes with a low detection limit (0.74×10-6 M for SE and 0.58×10-6 M for EP). The modulated sensor portrayed the supreme electrocatalytic characteristics toward the simultaneous quantification of SE and EP in a sample mixture.
Keywords: epinephrine